Perception and Adoption Level of Improved Off-season Tomato Cultivation Practice among Farm Women of Odisha - Nayak, U. S.; Das, S. R.; Shial, G. (International Journal of Bio-resource and Stress Management, 2020)
Study was undertaken in the selected villages of Keonjhar district of Odisha to assess the impact of Krishi Vigyan Kendra (KVK) intervention on the perception and adoption level of off-season tomato cultivation practices among the farm women. Profitability of small holder farm women can be improved by diversification through high value crops like vegetables during the off-season. The study area comes under North Central Plateau agro-climatic zone of the state which offered ample opportunities for the production of vegetables like tomato, cole crops, radish, coriander during the wet season, when the market demand for these vegetables are very high in comparison to the normal season. Realizing the potential of off-season vegetable production in improving the livelihoods of farming community, KVK, Keonjhar popularized this profitable venture through training and demonstration and after five years of intervention, the study for assessing the impacts revealed that the farmwomen of the KVK adopted villages had higher perception and adoption level on the important technologies of off-season tomato cultivation in comparison to the KVK non-adopted villages. However, their perception and adoption need to be improved in the areas like integrated nutrient and pest management practices in general and bio-fertiliser and bio-pesticide application, use of pheromone traps, selection of suitable safer insecticides and micronutrient application in particular. The personal and psycho-sociological attributes like participation level in training & demonstration, extension contact, exposure to best practices, farming experience, mass media exposure, progressiveness, scientific orientation, institutional orientation, education, social participation, communication behaviour and risk orientation had positive and significant association with the extent of adoption.